RANCANG BANGUN APLIKASI PENENTUAN PERSEDIAAN BERDASARKAN PERAMALAN VOLUME PERMINTAAN PADA UD. ADI JAYA MAKMUR - Rizal, Akhmad; Sulistiowati, Sulistiowati; Mastan, Iqnatius Adrian (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Adi Jaya Makmurâ€™s Company is a compnay that sell the materialâ€™s building. The address in Gubernur Sunandar Priyo Sudarmo 79 street, on Krian Sidoarjo. It offers some kind of materialâ€™s building which are cement, sand, brick, limestone, paints etc. The goods itâ€™s in Adi Jaya Makmurâ€™s Company are all collected from the supplier or manufacturers who has already become colleague in business for the further they can sell to the costumer. In Adi Jaya Makmurâ€™s company itself, they have trading system. Nowadays, we have a lot of rival in business which has effect on trading system volume unstable in Adi Jaya Makmurâ€™s company, especially in some materials, which are Gresikâ€™s cement, brick, sand and coral. The effect of the problemsÂ  are the inventory of the some variant of material are overfull rather than sales and the other side the inventory is empty or less so the costumer go to the next store. From the problems above, we make the inventory determinationâ€™s application based on the forecasting volume demand-based desktopÂ  with the title â€œ Designâ€™s Application Inventory Determination Based On The Forecasting Volume Demand On Adi Jaya Makmurâ€™s Companyâ€ which capable give a lot of contribution on the company to decide the storage on the next period. The method which is used to do the forecasting is Smoothing model expontial winterâ€™s method. This application that was made givingÂ  the information about the amount of demand for goods and also give for the next period. Based on the implementationâ€™s result and system evaluation, Designâ€™s Application Inventory Determination Based On The Forecasting Volume Demand On Adi Jaya Makmurâ€™s Company demand-based desktop will become the solution for the company to decide the amount of demand for goods to the next period.